2020
DOI: 10.1038/s41467-019-14161-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurology-related protein biomarkers are associated with cognitive ability and brain volume in older age

Abstract: Identifying biological correlates of late life cognitive function is important if we are to ascertain biomarkers for, and develop treatments to help reduce, age-related cognitive decline. Here, we investigated the associations between plasma levels of 90 neurologyrelated proteins (Olink® Proteomics) and general fluid cognitive ability in the Lothian Birth Cohort 1936 (LBC1936, N = 798), Lothian Birth Cohort 1921 (LBC1921, N = 165), and the INTERVAL BioResource (N = 4451). In the LBC1936, 22 of the proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 63 publications
6
43
0
Order By: Relevance
“…Synuclein is thought to be a marker of Parkinson’s disease and it has been studied in AD [ 11 ]. Protein arrays showed that ectodysplasin A2 receptor (EDA2R), Poliovirus receptor (PVR) and discoidin domain receptor family, member 1 (DDR1) were potential biomarkers of AD [ 12 ]. An array of nucleic acid aptamers was used to identify 44 proteins that apparently showed modest enrichments in AD but that showed no significant protein interactions, and APOE was the strongest correlate with amyloid burden [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synuclein is thought to be a marker of Parkinson’s disease and it has been studied in AD [ 11 ]. Protein arrays showed that ectodysplasin A2 receptor (EDA2R), Poliovirus receptor (PVR) and discoidin domain receptor family, member 1 (DDR1) were potential biomarkers of AD [ 12 ]. An array of nucleic acid aptamers was used to identify 44 proteins that apparently showed modest enrichments in AD but that showed no significant protein interactions, and APOE was the strongest correlate with amyloid burden [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…VWC2 (also known as the brorin) is expressed both in neural tissues in embryos and in neurons in the adult mouse brain and is involved in neurogenesis ( 43 ). In a recent study plasma EFNA4, CLM6, and VWC2 were negatively associated with general fluid cognitive ability in old individuals, an association that appeared to be mediated by brain volume ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…THBS4 encodes a secreted extracellular-matrix glycoprotein necessary for appropriate neuronal migration in the mouse 40 and is elevated 6-fold in the human cortex compared with non-vocal learning primates 41 . Human EDA2R was recently identified as a top correlate of cognitive performance and brain size 42 ; it was also found in a human GWAS study to correlate with circulating estrogen and testosterone levels 43 . Rare mutations in human PHETA1 lead to Lowe oculocerebrorenal syndrome, the pathophysiology that includes seizures, mental retardation, and structural brain abnormalities 44,45 .…”
Section: Gene Drivers Of E2-treated Female Hvc Specializationmentioning
confidence: 98%